Biomaterial‐Based Solid‐Electrolyte Organic Electrochemical Transistors for Electronic and Neuromorphic Applications. (17th October 2021) - Nguyen‐Dang, Tung; Harrison, Kelsey; Lill, Alex; Dixon, Alana; Lewis, Erin; Vollbrecht, Joachim; Hachisu, Taku; Biswas, Shantonu; Visell, Yon; Nguyen, Thuc‐Quyen
Abstract: A systematic study of biomaterial‐based solid‐state organic electrochemical transistors (OECTs) is presented in which biogels consisting of gelatin and glycerol, two food‐grade materials, are chosen as the model solid electrolyte. Such gels are fundamentally attractive for bioelectronics and wearable applications due to their superior and tunable electrical and mechanical properties, which allow one to fabricate solid‐state organic transistors with high ON/OFF ratio and transconductance, possible millisecond‐switching speed, and 6‐month stability in ambient air. Next, the authors show a good control of the state‐retention property of biogel OECTs, demonstrated herein by employing them as artificial synapses with various synaptic functions, such as frequency‐based short‐term plasticity. This study herein paves the way for the development of biomaterial‐based electronics by providing guiding principles for future works that employ biomaterials in OECTs. Abstract : A systematic study of biomaterial‐based solid‐state PEDOT:PSS organic electrochemical transistors (OECTs) is demonstrated, in which gelatin/glycerol biogels serve as the model electrolyte. By monitoring their temperature‐dependent operation, protons are shown to be the dedopants of PEDOT:PSS in these OECTs. Subsequently, biogel OECTs are fabricated with high transconductance, fast switching speed, long‐term stability, exhibiting several short‐term synaptic functions.